2009
DOI: 10.1371/journal.pone.0004405
|View full text |Cite|
|
Sign up to set email alerts
|

PD-1 Regulates Neural Damage in Oligodendroglia-Induced Inflammation

Abstract: We investigated the impact of immune regulatory mechanisms involved in the modulation of the recently presented, CD8+ lymphocyte mediated immune response in a mouse model of oligodendropathy-induced inflammation (PLPtg-mutants). The focus was on the role of the co-inhibitory molecule PD-1, a CD28-related receptor expressed on activated T- and B-lymphocytes associated with immune homeostasis and autoimmunity. PLPtg/PD-1-deficient double mutants and the corresponding bone marrow chimeras were generated and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…12 When investigating healthy 12-month-old PD-1 Ϫ/Ϫ and PLPtg/PD-1 Ϫ/Ϫ mice, we always detected higher numbers of peaks, 6 -9 indicating oligoclonal expansions, but no significant differences between these two groups. 24 To our knowledge, this is the first study describing clonal expansions in BL/6 mice during EAE. Interestingly, there was no difference in the number of oligoclonal expansions between PLPtg and wild-type mice, which both displayed approximately eight to nine oligoclonal expansions, whereas in the absence of PD-1, independent from an additional myelin mutation, the number was approximately twice as high (17 and 15, respectively).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…12 When investigating healthy 12-month-old PD-1 Ϫ/Ϫ and PLPtg/PD-1 Ϫ/Ϫ mice, we always detected higher numbers of peaks, 6 -9 indicating oligoclonal expansions, but no significant differences between these two groups. 24 To our knowledge, this is the first study describing clonal expansions in BL/6 mice during EAE. Interestingly, there was no difference in the number of oligoclonal expansions between PLPtg and wild-type mice, which both displayed approximately eight to nine oligoclonal expansions, whereas in the absence of PD-1, independent from an additional myelin mutation, the number was approximately twice as high (17 and 15, respectively).…”
Section: Discussionmentioning
confidence: 85%
“…Second, the absence of the coinhibitory molecule PD-1 induced a stronger inflammatory stimulus, and the combination of both culprits resulted in the accelerated, stable, homogenous exacerbation of disease. Importantly, the combination of the two factors without EAE induction already led to an aggravation of myelin and axon damage 24 but at a much later time point. It is tempting to speculate that, in the young double mutants, a not yet visible predisposition for severe inflammatory disease progression already exists and becomes triggered by EAE induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD-1 and its ligands were found to be strongly expressed on immune infiltrates in the CNS during the peak phase of EAE (9)(10)(11). In EAE studies, PD-1-deficient mice or the use of blocking antibodies that inhibit PD-1 engagement by ligands resulted in earlier disease onset, increased inflammatory infiltrates, and increased severity of clinical symptoms compared with normal disease progression (10)(11)(12)(13)(14)(15)(16). It has been demonstrated that ligand engagement of PD-1 inhibits T-cell activation, expansion, and cytokine production (17)(18)(19).…”
mentioning
confidence: 99%
“…8,9 By histological luxol fast staining, a severely reduced myelin was observed in rat pups born from irondeficient dams, 10 and mice made iron deficient from gestation up to the postnatal age of 75 days showed significant alterations in myelin fatty acid composition compared to control and iron-replete groups. 11 In Sprague-Dawley rats, alterations of myelin molecular and metabolic activity markers as well as in fatty acid composition were determined in hind brain myelin from pre-and postweaning pups, 12 alterations which behaviourally were mirrored by an experimental animal model.…”
Section: Introductionmentioning
confidence: 99%